Mittani palaeography - Homan, Zenobia (Cuneiform monographs, 2020)
"In Mittani Palaeography, Zenobia Homan analyses cuneiform writing from the Late Bronze Age Mittani state, which was situated in the region between modern Aleppo, Erbil and Diyarbakır. The ancient communication network reveals a story of local scribal tradition blended with regional adaptation and international political change, reflecting the ways in which written knowledge travelled within the cuneiform culture of the Middle East. Mittani signs, their forms, and variants, are described and defined in detail utilising a large digital database and discussed in relation to other regional corpora (Assyro-Mittanian, Middle Assyrian, Nuzi and Tigunanum among others). The collected data indicate that Mittanian was comparatively standardised - an innovation for the period - signifying the existence of a centralised system of scribal training"--